Kazakh tea ceremony: traditions and innovations - Naymova, O; Мeirmanova, G; Baydiarova, K (Farabi Journal of Social Sciences, 2019)
Today it is impossible to imagine the Kazakh meal without tea. However, it entered the everyday life of the Kazakhs relatively recently. For centuries, the basis of the life of the Kazakhs was nomadic transhumance cattle breeding, in which sheep and herd horse breeding prevailed. This type of economy for a long time determined the specificity of the somewhat monotonous Kazakh cuisine, which was based mainly on the use of meat and milk, as well as a small number of grain products, in particular millet. However, from the end of the XVIII century. Fundamentalchanges in the political and, as a result, economic life of the Kazakhs began. They entailed a process of settling on the land, more frequent contacts with neighboring nations; In the Kazakh diet began numerous borrowings and distribution of new products. Purpose of the study аt the end of XIX century in the diet of the Kazakhs, along with the name (the Kazakhs call it shai) tea is firmly entered. Key words: tea, cattle breeding, diet of the Kazakhs, meat and milk, economic life of the Kazakhs.